The effect of inter-laboratory variability on the protein:creatinine (UPC) ratio in canine urine. Issue 1 (April 2015) - Rossi, G.; Bertazzolo, W.; Dondi, F.; Binnella, M.; Gruarin, M.; Scarpa, P.; Paltrinieri, S.
Highlights: Inter-laboratory variability may affect the urine protein:creatinine (UPC) ratio. We measured the UPC ratio in the same canine samples in three different laboratories. UPC ratio was significantly different most likely due to different methods or instruments. Despite this, the concordance in classifying proteinuric dogs was very good. Inter-laboratory variability may affect patient monitoring during follow up. Abstract: Quantification of proteinuria is a fundamental step in staging dogs with chronic kidney disease and in monitoring the course of disease or the efficacy of anti-proteinuric treatments. Analytical precision and accuracy of the proteinuria assessment could be affected by several factors such as biological variability, different operators and quality control materials. The aim of this study was to assess whether inter-laboratory variability could affect the urinary protein to creatinine (UPC) ratio and whether this variability may affect patient classification according to the International Renal Interest Society (IRIS) sub-staging system. The same urine samples were analysed in three different laboratories using different instruments and different reagent brands. The results of the three laboratories were highly correlated to each other although urinary protein (UP), urinary creatinine (UC) and the UPC ratio of one laboratory were found to be significantly higher than those of the other two. No significant differences between the other two laboratories were recorded. The concordance in classifying dogs according to the IRIS guidelines was good if all three proteinuria categories were analysed separately or if borderline proteinuric (BP) dogs were included in the proteinuric group, and very good if BP dogs were merged into the non-proteinuric group. The inter-laboratory variability in UPC ratio measurement was not so great as to impede the identification of proteinuric dogs, but may influence the estimation of the magnitude of proteinuria.